The influence of oxygen as impurity substitution defects on the electronic structure of binary graphene - V. V. Bolotov; V. A. Sachkov (Омский научный вестник)
The paper is devoted to the study of the effect of oxygen as an impurity substitution defect in single-layer and double-layer graphene planes on the electronic properties of these structures. The van der Waals interaction is studied for the electronic properties of paired graphene planes of the substitution type for an impurity oxygen atom. Calculations of the «ab initio» electronic zone structure of the studied objects are made. The results obtained are applicable to the analysis of the zone structure of multi-wall carbon tubes containing defects.